Evaluation of linear growth at higher altitudes - Baye, Kaleab; Hirvonen, Kalle (American Medical Association, 2020)
Irrespective of their genetic makeup, children living in an ideal home environment that supports healthy growth have similar growth potential. However, whether this potential is true for children residing at higher altitudes remains unknown.